2020
DOI: 10.3389/fgene.2020.00250
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 Interacted With DNMT1 to Regulate Malignant Phenotype of Cancer Cell and Cytotoxic T Cell Infiltration via Epigenetic Inhibition of p53, cGAS, and STING in Lung Cancer

Abstract: Purpose: Lung cancer is the main cause of cancer-related mortality worldwide. We report here the biological role of nuclear paraspeckle assembly transcript 1 (NEAT1) in the pathogenesis of lung cancer and the underlying mechanisms. Methods: Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and Western blotting analysis were used to evaluate expression of mRNA and protein. RNA immunoprecipitation (RIP) assay, chromatin immunoprecipitation followed by qPCR analysis, and reporter assay were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 37 publications
5
65
0
Order By: Relevance
“…In another study, lncRNA NEAT1 was shown to facilitate the progression of gallbladder cancer via the upregulation of Survivin expression, suggesting its potential use as a biomarker in gallbladder cancer 34 . Multiple other studies show NEAT1 associations with osteoarthritis 35 , lung cancer 36 , and acute myeloid leukemia 37 . USP3-AS1 has also been reported as a potential biomarker for neuroblastoma pathogenesis studies 38 .…”
Section: Discussionmentioning
confidence: 91%
“…In another study, lncRNA NEAT1 was shown to facilitate the progression of gallbladder cancer via the upregulation of Survivin expression, suggesting its potential use as a biomarker in gallbladder cancer 34 . Multiple other studies show NEAT1 associations with osteoarthritis 35 , lung cancer 36 , and acute myeloid leukemia 37 . USP3-AS1 has also been reported as a potential biomarker for neuroblastoma pathogenesis studies 38 .…”
Section: Discussionmentioning
confidence: 91%
“…The activation of the STING signaling pathway in small cell lung cancer (SCLC) also enhances the protective effects of immunotherapy ( 157 ). Another study has indicated that the cGAS-STING signaling pathway inhibition due to upregulated nuclear paraspeckle assembly transcript 1 (NEAT1) in the lung cancer cells and tissues ( 158 ). NEAT1 interacts with DNA (cytosine-5)-methyltransferase 1 (DNMT1) to inhibit tumor suppressor p53 and cGAS-STING expression.…”
Section: Cgas-sting-based Host Cell Dna Recognitionmentioning
confidence: 99%
“…Both HSV-1 infection and IFN-α treatment induce cGAS mRNA expression in neonatal PBMCs from 1-month-old infants ( 77 ). LncRNA NEAT1 epigenetically inhibits cGAS expression to regulate the malignant phenotype of cancer cells and cytotoxic T cell infiltration in lung cancer ( 78 ).…”
Section: Transcriptional Regulation Of Nuclear Dna Sensorsmentioning
confidence: 99%